2016
DOI: 10.5130/ajceb.v16i1.4662
|View full text |Cite
|
Sign up to set email alerts
|

Organisational life cycle, business orientation and performances of architectural firms in Nigeria

Abstract: This study sets out to investigate the relationships between the organisational life cycles, business orientation and performances of architectural firms, which often start with just the principal and little capital. In the study, the organisational life cycles stages of the firms were identified, and the way that business orientation emphasis changes with the firms’ life cycles were investigated. In addition, the business orientation dimensions that predict the architectural firms’ performance at each life cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…These results when compared and contrasted against previous empirical results can be classified into three. The first group that agrees with the findings of this study are Wahba and Elsayed (2014), Hossain (2014), Gunu and Adamade (2015), Oluwatayo et al (2016), Zhou et al (2016), Gulec and Karacaer (2017) and Costa et al (2017). However, the second group completely disagrees with the findings of this study and they include Chang et al (2017), Habib and Hassan (2017), Bayat and Noshahr (2018) and Shahzad et al (2019).…”
Section: Data Analysis and Interpretationsupporting
confidence: 48%
See 1 more Smart Citation
“…These results when compared and contrasted against previous empirical results can be classified into three. The first group that agrees with the findings of this study are Wahba and Elsayed (2014), Hossain (2014), Gunu and Adamade (2015), Oluwatayo et al (2016), Zhou et al (2016), Gulec and Karacaer (2017) and Costa et al (2017). However, the second group completely disagrees with the findings of this study and they include Chang et al (2017), Habib and Hassan (2017), Bayat and Noshahr (2018) and Shahzad et al (2019).…”
Section: Data Analysis and Interpretationsupporting
confidence: 48%
“…An inverse relationship was found existing between firm introductory stage and financial performance. Also, Oluwatayo et al (2016) examine the influence of organisation's life cycle on performance of architectural firms in Nigeria. The findings indicate that at maturity, organisation's performance varies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, several studies have reported negative innovation effects on company financial performances. For example, innovation negatively affected the financial performances of architectural companies in Nigeria due to the speculative nature of the industry (Oluwatayo et al , 2016) and contrary to other studies, Zhu et al (2017) found that only marketing innovations improved small and medium enterprises (SME) economic performances in Zhejiang Province, China. These contradictions suggested that other variables were mediating and/or moderating the positive relationship between innovation and financial performance.…”
Section: Introductionmentioning
confidence: 70%
“…While construction companies differ in size, knowledge and risk attitude (Lew et al , 2018; Teräväinen et al , 2018), two of the most important actors in the industry are architects and contractors (Hemstrom et al , 2017; Sariola, 2018). Architecture companies are professional service companies that are generally knowledge intensive, relatively small in size and often led by the principal architects (Hong et al , 2019; Oluwatayo et al , 2016; Salvatierra et al , 2019). Conversely, large companies usually dominate the contractor market, with others being mainly small and medium sized, labour intensive and typically family-owned (Teräväinen and Junnonen, 2019; Hong et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The success of each organization in its life cycle is determined by its ability to choose and make effective use of the resources [30]. In the context of digital economy, the company's physical resources cannot be maintained as an evolutionary asset because it is relatively easy to buy and imitate [31] in contrast to intangible resources such as competency.…”
Section: Competency Development (Cd)mentioning
confidence: 99%